(untitled) (Journal of Educational Sciences, 2016)
The article deals with peculiarities of teaching foreign students the Russian language at the initial stage. The purpose of the article is the generalization of practical innovative experience in teaching Russian as a foreign language. A brief review of the learning styles of students, which allows the teacher to plan more effectively the work of the class and the student to improve motivation and more effective to learn the language. Special attention is paid to the factors preventing the rapid pace of learning and mastery of the material. Considered age, ethnicity, social characteristics of students, influencing the formation of the learning process. Polyethnic groups of students can be not only difficult moment in the training group, but also become a strong side of the formation, due to the methodical skill of the teacher. From practical experience are offered the most effective types of work, facilitating the process of mastering a foreign language Russian as a foreign language.